Application Values of T-SPOT.TB in Clinical Rapid Diagnosis of Tuberculosis - Feng ZHU; Qinfang OU; Jian ZHENG (Iranian Journal of Public Health, 2017)
Background: This paper aims to explore the application value of tuberculosis-specific enzyme-linked immunospot assay (T-SPOT.TB) in the diagnosis of tuberculosis.